Keanekargaman Spesies Burung di Sekitar Dukuh Sokokembang, Kecamatan Petungkriyono, Kabupaten Pekalongan - Wisnumurti, Arya Bahari; Santoso, Joko Santoso Joko; Wibowo, Dwi Nugroho (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
Indonesia has 1.794 species of birds with 527 of them are endemic in Indonesia. Birds have ecological benefits such as 1) pollinators, 2) pest controller, 3) supports the ecosystem. Eggs, flesh, feathers even nests have economical values that can be used as food, clothes or accessories. The species of bird has a trend of decreasing. Studies of bird species in there habitat need to be done periodly to prevent the trend to continue. The goal of this study is to identify the species of birds near Sokokembang. Observation methode with the point count technique is used in this study in July and December 2022. About 15 species of birds are found with in there are N. bartelsi and H. cyanoventris are found as endemic species. The finding of this study reveal that they are 6% of the findings found in preveous studies with 9 similar species and 6 different species. Ajusting by the conservation status in IUCN and Data Burung Indonesia, 1 species is categorized as Endangred and 14 species are categorized Least Concerned. Information of the species of birds need to be periodly evaluated so the proper act of conservation can be used to maintain the abundance of species of birds in Petungkriyono.